FeOx nanoparticle doping on Cu/Al2O3 catalysts for the reverse water gas shift. (October 2022) - Pahija, Ergys; Panaritis, Christopher; Rutherford, Brian; Couillard, Martin; Patarachao, Bussaraporn; Shadbahr, Jalil; Bensebaa, Farid; Patience, Gregory S.; Boffito, Daria C.
Abstract: Coal-based electricity generation surged 22% in 2021 versus 2019 in the USA due to high natural gas prices and ease of transportation. This contradicts societies desire to produce clean energy and underscores the urgency to develop technologies to capture atmospheric CO2 and produce value-added products. The reverse water gas shift (RWGS) converts CO2 to CO, which is a basic intermediate for the chemical and petrochemical industries. Fe is the prime catalyst metal for this reaction and here we compare the activity of Fe clusters and 5 nm FeOx nanoparticles deposited on Cu/Al2 O3 . The catalytic activity towards the RWGS increases as a function of Fe doping. Fe clusters doping are non-uniform in size on Cu/Al2 O3, whereas FeOx nanoparticles synthesized with the polyol method are uniform and well-dispersed on the Cu surface. The interaction between Cu and FeOx establishes a dual catalyst where FeOx and Cu activate CO2 and H2, respectively, an effect that is functionally equivalent to the metal-support interaction phenomenon. Furthermore, FeOx on Cu/Al2 O3 (0.009 g g −1 of Fe) converts 2-times more CO2 than un-doped Cu/Al2 O3 with a CO selectivity > 99%. Our method provides a technique to dope synthesized catalysts with nanoparticles to enhance their catalytic activity, selectivity and stability. Highlights: Unprecedented CO2 conversion in the Reverse Water Gas Shift at 300 °C: 5%. Eight CuFe catalysts supported on Al2 O3 were synthesized. CuFe/Al2 O3 was 99%+ selective to CO. FeOx nanoparticle doping increased the CO2 conversion by 50%. We demonstrate the synergistic effect for the dual catalyst FeOx and Cu.